Legal Analysis of Material Control in Motor Vehicle Registration and Identification (Regident) as an Administrative Instrument - Faathir Firdhilianto (Indonesian Journal Publisher, 2026)
Motor Vehicle Registration and Identification (Regident Ranmor) is a state administrative instrument that plays a crucial role in regulating traffic and road transportation in Indonesia. Control of the Registration Material through the Vehicle Registration Certificate (BPKB), Vehicle Registration Certificate (STNK), and Vehicle Registration Certificate (TNKB) not only serves as ownership administration but also as a means of monitoring, law enforcement, and preventing motor vehicle crime. This study aims to analyze the legal basis and objectives of implementing the Registration Material control for motor vehicles based on applicable laws and regulations, specifically Law Number 22 of 2009 concerning Road Traffic and Transportation, and to assess its effectiveness in maintaining data validity and preventing vehicle crime from an administrative law perspective. The research method used is normative legal research with a statutory and conceptual approach. The results indicate that the Registration Material control has a strong legal basis as a form of government administrative legal action (bestuursdaad) to ensure legal certainty, traffic order, and public safety. The implementation of the Electronic Registration and Identification (ERI) system improves data accuracy and supports the prevention of motor vehicle crime, although strengthening data integration and administrative oversight is still needed.